Océan Atlantique nord, abords sud de Terre-Neuve, Ile St. Pierre / levée en 1841 . Dépôt général de la marine, 1843 - France. Dépôt général de la marine (1931)
Édition d'Août 1918. Corr. . 1931 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange and red.; Includes 5 coastal profiles and 2 pasteovers Grayscale; 1:17,800